MENINGKATKAN KEPUASAN PELANGGAN MELALUI PERAN KUALITAS PELAYANAN: KEPUTUSAN PEMBELIAN SEBAGAI MEDIATOR:Riset Pelanggan Ammal Marwah Tour (Pembelian Tiket Maskapai Penerbangan) - Nasrudin Laope; Darwin Raja Unggul Saragih (LPPM and Travel Operation Department Universitas Asa Indonesia, 2022)
This research is entitled “Improving Customer Satisfaction Through the Role of Service Quality: Purchasing Decisions as Mediator: Ammal Marwah Tour Customer Research (Purchase of Airline Tickets). Aims to analyze the effect of service quality on satisfaction and is mediated by purchasing decisions. Collecting data by distributing questionnaires to Ammal Marwah Tour customers by applying purposive sampling criteria with the criteria of customers who have purchased airline tickets at least twice. Samples obtained from distributing questionnaires were 135 and those who passed the sample test for data processing were 117 and 20 were used as sampling. The data were processed with the Smart PLS program. It is concluded from the research results that service quality has an influence on purchasing decisions and customer satisfaction as well as purchasing decisions as a mediator.